2008
DOI: 10.1371/journal.pone.0004046
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of GSK3β by the Phosphorylated Cytoplasmic Domain of LRP6 in Wnt/β-Catenin Signaling

Abstract: Wnt/β-catenin signaling plays a central role in development and is also involved in a diverse array of diseases. Binding of Wnts to the coreceptors Frizzled and LRP6/5 leads to phosphorylation of PPPSPxS motifs in the LRP6/5 intracellular region and the inhibition of GSK3β bound to the scaffold protein Axin. However, it remains unknown how GSK3β is specifically inhibited upon Wnt stimulation. Here, we show that overexpression of the intracellular region of LRP6 containing a Ser/Thr rich cluster and a PPPSPxS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
211
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(220 citation statements)
references
References 35 publications
9
211
0
Order By: Relevance
“…2) (Mao et al 2001b). This critical but unresolved issue has fueled an alternative model in which LRP6-Axin interaction may be indirectly mediated by other factors such as GSK3 (Piao et al 2008). …”
Section: Lrp6 Phosphorylation and Axin Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…2) (Mao et al 2001b). This critical but unresolved issue has fueled an alternative model in which LRP6-Axin interaction may be indirectly mediated by other factors such as GSK3 (Piao et al 2008). …”
Section: Lrp6 Phosphorylation and Axin Recruitmentmentioning
confidence: 99%
“…This region is likely phosphorylated by CK1, including the nearby T1479 by CK1g (Davidson et al 2005). The functional significance of this S/T cluster is unclear, although one study suggests it as a GSK3-binding site upon CK1 phosphorylation (Piao et al 2008). Secondly, there exist seven mammalian CK1s (a, b, g1, g2, g3, d, and 1) (Price 2006).…”
Section: Lrp6 Phosphorylation: Kinases and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Binding of the axin-GSK-3b complex to phosphorylated LRP6 inhibits GSK-3b activity allowing cytoplasmic b-catenin to stabilize. 36,37 Thus, GSK-3b in the destruction complex promotes b-catenin degradation, whereas GSK-3b-mediated phosphorylation of LRP6 at the plasma membrane in response to Wnt binding to Fz receptors contributes to the stabilization of b-catenin. Taken together, Wnt binds to Fz-LRP5/6 complex and induces Fz recruitment of Dvl, which in turn recruits the axin-GSK-3b complex to the membrane, and thereby promotes LRP5/6 phosphorylation to initiate an active b-catenin signaling.…”
Section: Canonical Wnt Pathwaymentioning
confidence: 99%
“…To confirm the inhibition effect of GN chemical on p53-Snail binding, we designed following experiment; in previous, we have found that Snail middle region, which is also responsible for binding with p53 (Lee et al, 2009c), is phosphorylated by CK1/GSK3b (Cano et al, 2000;Yook et al, 2006). Thus, addition of recombinant p53 could block the CK1/GSK3b-mediated Snail phosphorylation, whereas p53 did not affect CK1/GSK3b-mediated b-catenin phosphorylation (Piao et al, 2008;Ha et al, 2004;Supplementary Figure S5E). However, addition of quercetin, specific inhibitor against p53-Snail binding (Lee et al, 2009a, c), or GN25 could recover the CK1/GSK3b-mediated Snail phosphorylation in the presence of p53 (Figures 3f and g).…”
Section: Specific Inhibition Of P53-snail Bindingmentioning
confidence: 82%